Molecular regulation of human interleukin 2 and T-cell function by interleukin 4. - Schwarz, E M (1993)
Distinct functional T-cell subsets, differing in the patterns of lymphokines produced, regulate cell-mediated and humoral immune responses. The two major types and their principal products, interleukin 4 and interferon gamma (IL-4 and IFN-gamma), are reciprocally negatively interactive. To analyze the molecular mechanism of IL-4-mediated suppression of cell-mediated immunity we studied its effects on expression of interleukin 2 (IL-2) and IFN-gamma. IL-4 pretreatment of Jurkat cells prior to stimulation resulted in a decrease in transcription of the IL2 gene. IL-4 suppressed IL-2 and IFN-gamma mRNA levels in primary human T cells, and addition of anti-CD28 antibodies relieved this suppression. Using enhancer-reporter constructs, IL-4 specifically down-regulated the NFIL-2B element. Electrophoretic mobility shift assays using a DNA oligomer containing the NFIL-2B binding site indicated that IL-4 inhibited the NFIL-2B complex and that the NFIL-2B DNA binding factor is distinct from AP-1. These results suggest that IL-4 may regulate development and function of T-cell subsets involved in cell-mediated immunity in part by inhibiting factors required for transcription of the IL2 gene.